The Changes of Nutrient Composition and In Vitro Evaluation on Gamma Irradiated Sweet Sorghum Bagasse - Teguh Wahyono; Firsoni Firsoni (BATAN, 2016)
In vitro rumen fermentation study was done to evaluate the effects of gamma irradiation on nutrient compound changes and rumen fermentation product of sweet sorghum bagasse (SSB). The level doses 0, 50, 100 and 150 kGy from cobalt-60 gamma rays irradiator was used to treate sweet sorghum bagasse (SSB). Variables measured were nutrient values, gas production, methane (CH4) production, total volatile fatty acid (TVFA), ammonia (NH3), in vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD) after 72 h in-vitro incubation times. Complete randomized design (CRD) (four treatments and four replications) was used to analyze data. The results showed that gamma irradiation doses of 50, 100 and 150 kGy were able to reduce neutral detergent fibre (NDF) (2.15; 3.29 and 5.44% respectively) and acid detergent fibre (ADF) (3.29; 4.58 and 4.58% respectively) and significantly different (P<0.05). Gamma irradiation was capable to increas total volatile fatty acid (TVFA), IVDMD and IVOMD (P<0.05). Irradiation doses of 100 and 150 kGy also increased protozoa population and CH4 production significantly (P<0.05). Gamma irradiation improved in vitro rumen performance represented in rumen fermentation products. Keywords : Gamma irradiation, In vitro fermentation, Nutrient composition, Sweet sorghum bagasse